Resistência genética e induzida de Vigna unguiculata (L.) Walp. à Aphis craccivora Koch e sua amostragem. - Silva, Jefté Ferreira da (2011)
The objective of this work were: to evaluate resistance of cowpea genotypes [Vigna unguiculata (L.) Walp.] to the black aphid [Aphis craccivora Koch, 1854] and to study the genetic variability of these genotypes for this feature; to evaluate the possible inducible action of cis-jasmone to resistance to this pest; to study the spatial dispersion of the aphid in cowpea culture, and to establish the number of samples required to estimate the population of the pest to use in integrated pest management programs. To evaluate the resistance preference, an experiment was conducted in a greenhouse at the Universidade Federal do Ceará (UFC) in Fortaleza, Ceará. The experimental design was randomized blocks with 51 treatments, represented by genotypes and four replications. We estimated the generalized Mahalanobis distances and grouping of genotypes was performed using the Tocher optimization method. For the evaluation of cis-jasmone three experiments were conducted, the first in Quixadá, Ceará, in the design of randomized blocks with five replications and five treatments as follow: untreated control; application of the insecticide endosulfan and deltamethrin, and the application of cis-jasmone a single dose of 60 g.ha-1, three applications of 20 g ha-1 and six of 10 g ha-1 on the cultivar Vita 7. In the second, in the same place, the seeds of the TVu 408 P2, BRS Gurguéia and Vita 7 were soaked in a solution of cis-jasmone with 60 g ha-1 or in water for 24 hours. The design was factorial 3x2 in blocks. In the third experiment, conducted in the UFC, we used a randomized block design with four replications and four treatments consisting of an untreated control, and applications of cis-jasmone at doses of 50 g ha-1, 100 g ha-1 and 200 g ha-1. The cultivar was Vita 7. For the evaluations, the number of colonies of aphids present in every plant was counted. To evaluate the spatial distribution of aphid were grown in two field trials in the UFC. The first field had an area of 216 m² and second 576 m². The fields were divided into 15 and 25 plots, respectively. The cultivar used was Vita 7 spaced in 0.25 m x 0.8 m. On those fields were performed six collections of data in each field where they were evaluated ten plants per plot. It was count the number of colonies of aphids present throughout the plant. The results show that the genotypes BRS Guariba, TVu 410, BRS Paraguaçu TVu 36, Sempre Verde, TVu 408 P2, Setentão e Epace 10 have greater resistance to the aphid than the others. The largest differences were found between BRS Guariba and Sete Semanas and between Tvu 410 and Sete Semanas, while the BRS Guariba and TVu 410 were the most similar. We observed the division of the genotypes in eight groups and the character that contributes to the most divergence was the number of nymphs. The crosses among the genotype Setentão and the genotypes BRS Guariba ,TVu 410, BRS Paraguaçu, TVu 36, TVu 408 P2 and between Epace 10 and Sempre Verde, BRS Guariba and TVu 410 may result in new genetic combinations intended to improve resistance to aphid. In all experiments, cis-jasmone did not reduce the infestation of A. craccivora and so concluding that this product, under field conditions, does not induce resistance. The dispersion indices indicate that aggregate was the case in this study, which was confirmed by data fitting the frequency distribution of the Negative Binomial. Forty five is the appropriate number of samples to estimate the population of A. craccivora in the fields of V. unguiculata to be used in Integrated Pest Management programs.